Pengaruh Kompetensi Sumber Daya Manusia, Sistem Pengendalian Intern, dan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pemerintah Daerah(Studi Empiris pada Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah (DPPKAD) Kabupaten Sukoharjo) - Wijayanti, Lilis; , Drs. Atwal Arifin, M.Si, Ak.CA (2017)
The purpose of this study was to determine the effect of human resource competency,internal control system and the utilization of information technology on the Quality of local Government Financial Report (LKPD) in DPPKAD of Sukoharjo regency. The used sampling method is the saturated samples. Data collection is done by giving as many as 86 copies of the questionnaire, which was distributed to respondents on DPPKAD of Sukoharjo Regency. The data obtained are then analyzed using SPSS 21.00. Based on the analysis result, obtained that the human resource competency has unsignificant effect on the Quality of local Government Financial Report (LKPD) in DPPKAD of Sukoharjo regency, internal control system and the utilization of information technology has significant effect on the Quality of local Government Financial Report (LKPD) in DPPKAD of Sukoharjo regency.